If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 1 + -7 Combine like terms: 1 + -7 = -6 0 = -6 Solving 0 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2(x-3)+2(3x-3)=2x+2(2x-1) | | 3(6-z)+6z= | | .1/x=90 | | 2x-22=-3x+28 | | 18-6a=4a-4a-12 | | 3+2[x-9]=12-7x | | .1*x=900 | | X-5+6x-23=3x+2 | | 7x-4(6-x)+12= | | p-9b/13c-7 | | .1-x=900 | | 5(x+4)=-50 | | 5x-13y+10y= | | 56m^13n^6/8m^12n^3 | | 3x-18=-x+30 | | 8(2b-7)=4(b+10) | | 6x-3x-12= | | 1.04p=124.8 | | 2340=(n-2)180 | | h=5+27t-16t^2 | | -5=-1.60(4)+b | | 7x+19x+13x= | | x^2-y^2=100 | | 96=2(5x+3)+2(4x) | | -4x-27=7x+7 | | y-b=nyb | | x^3y^2+5x^2y-14x=0 | | 5(x+4)+(3x-5)= | | 208=2(5z+2)+2(4z+3) | | 68=.2(20x+50)+2 | | y=-1.60x+b | | -9x^2+35x-30=1-x |